2011
DOI: 10.1002/cae.20548
|View full text |Cite
|
Sign up to set email alerts
|

Web‐based 3D medical image visualization framework for biomedical engineering education

Abstract: Medical imaging is one of the major fields in the multi-disciplinary curriculum of biomedical engineering (BME). Biomedical engineers from different backgrounds need to understand biology in order to be able to develop effective equipment to improve healthcare diagnosis through medical images. Visualization tools are important in the learning process to improve biomedical engineer's understanding of medical imagery. In this work, we design a web-based 3D medical image visualization framework that can be used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Settapat et al design a web‐based 3D medical image visualization framework that can be used to improve medical image understanding in biology and anatomy.…”
Section: Interactivitymentioning
confidence: 99%
“…Settapat et al design a web‐based 3D medical image visualization framework that can be used to improve medical image understanding in biology and anatomy.…”
Section: Interactivitymentioning
confidence: 99%
“…The judgment of whether the research has selective reporting is based on whether the results are fully mentioned in the manuscript or discussion section. Three studies were judged to be at high risk of other bias as the experimental or control group had fewer than 10 participants [15,19,49]. Finally, one study was judged to have a high risk of performance bias due to the participants' biased understanding of the assigned interventions during the study period [19].…”
Section: Literature Quality Analysismentioning
confidence: 99%
“…Ten studies [19,27,31,38,40,42,45,47,49,50] evaluated satisfaction as a secondary outcome (Fig. 5A).…”
Section: Data Merging Of Satisfaction Degreementioning
confidence: 99%
See 1 more Smart Citation
“…Online remote 3D visualization is also widely used in the field of medical teaching. 21,27,28 Tan et al 29 showed that not only are students enabled to observe the construction of a human skeleton anatomy model more intuitively to stimulate their interest in learning, but also teacher lesson preparation efficiency and teaching effect are improved by constructing a new teaching platform of a Web-based 3D human skeleton anatomy model. However, these methods are seldom used in the field of medical tele-diagnosis, which requires high interactive speed and 3D image reconstruction quality.…”
Section: Related Workmentioning
confidence: 99%